A dual-mode orthogonal three-primary color luminescent nanoparticle, multi-level anti-counterfeiting material, and preparation method and application thereof

By adopting a dual-mode orthogonal three-primary color luminescent nanoparticles with core-shell-shell-shell structure, the concentration and types of rare earth ions are regulated, and a multifunctional orthogonal red, green and blue three-primary color luminescent at the level of a single nanoparticle is solved, and the existing nanoparticles have complex structure and single functions are solved.

CN116103032BActive Publication Date: 2025-04-15JIANGXI UNIV OF SCI & TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211101077.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-09
Publication Date
2025-04-15
Estimated Expiration
2042-09-09

AI Technical Summary

Technical Problem

Existing nanoluminescent particles can only realize the three primary color orthogonal luminescence in a single mode, and the structure is complex and difficult to achieve multifunctional environmental response.

Method used

Dual-mode orthogonal tri-primary color luminescent nanoparticles adopting core-shell-shell-shell structures, by regulating the concentration and types of rare earth ions of the crystal core and shell, up-converting green/red and blue light emission, and down-transferring red/green light emission.

Benefits of technology

At the level of single nanoparticles, the orthogonal red, green and blue three-primary color luminescence responding under near-infrared and near-ultraviolet wavelength excitation is achieved, solving the problems of complex structure and single function of traditional nanoparticles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116103032B_ABST
    Figure CN116103032B_ABST
Patent Text Reader

Abstract

The present invention provides a dual-mode orthogonal tri-primary color luminescent nanoparticle, a multi-level anti-counterfeiting material, and a preparation method and application thereof, and relates to the technical field of luminescent materials. The chemical composition of the nanoparticle provided by the present invention is NaGdF 4 :Yb / Ho / Ce@NaYF 4 :M@NaYF 4 :Yb / Tm@NaYF 4 :Yb / Nd, among which Ce in the crystal core 3+ The concentration of Gd is 0.5-40 mol%, and M is Eu or Tb. 3+ The interfacial energy transfer characteristics of Ce 3+ with Ho 3+ By combining cross-relaxation between the two layers and the multifunctional effect of the first emission shell layer (red light or green light emission layer and an inert protective layer), the up-conversion / down-transfer dual-mode orthogonal red, green and blue primary color luminescent nanoparticles are realized, which respond under excitation of near-infrared and near-ultraviolet wavelengths. The anti-counterfeiting material made of the nanoparticles is highly secure, not easy to be copied, and has a high level of security and anti-counterfeiting.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of luminescent materials, and in particular to a dual-mode orthogonal three-primary-color luminescent nanoparticle, a multi-level anti-counterfeiting material, and a preparation method and application thereof. Background Art

[0002] Lanthanide ion-doped upconversion nanoparticles (UCNPs) are one of the most promising luminescent nanomaterials and have attracted much attention due to their unique nonlinear anti-Stokes luminescence. Based on the unique 4f electronic configuration and rich energy level transitions of lanthanide ions, UCNPs have the characteristics of large anti-Stokes shift, adjustable luminescence color, narrow emission bandwidth, long fluorescence lifetime, high luminescence stability, and low background interference, and have potential application prospects in the fields of bioimaging, therapy, and life sciences.

[0003] Ideal multifunctional UCNPs should have different emission channels, be able to give corresponding color responses according to changes in the environment, and adjust their emission wavelength from ultraviolet light to multicolor emission in the visible light range. However, under fixed single wavelength excitation, traditional UCNPs can only emit light of a fixed color. UCNPs with orthogonal excitation-emission (OUCNPs) can selectively activate lanthanide activators located in different shell components by changing external excitation conditions, thereby achieving different luminescent colors under different excitations. This type of novel emission regulation characteristics has received increasing attention.

[0004] For example, Chinese patent CN111681532A discloses a core-shell structure nanoparticle with red, green and blue primary colors orthogonal luminescence, which is composed of a NaYF4 main matrix doped with a sensitizer and an activator; the sensitizers are Er 3+ 、Nd 3+ and Yb 3+ ions and activators are Ho 3+ , Er 3+ and Tm 3+Ions; core-shell structure nanoparticles are composed of core NaYF4:Yb / Tm, first inert isolation layer NaYF4, red light emitting layer NaYF4:Er / Ho, second inert isolation layer NaYF4, green light emitting layer NaYF4:Nd / Yb / Er and energy absorption layer NaYF4:Nd from the inside to the outside. Chinese patent CN111808604A discloses a core-shell structure material: NaYF4:Yb / Tm@NaYF4@NaYF4:Er / Ho@NaYF4@NaYF4:Nd / Yb / Er@NaYF4:Nd, which can respond to orthogonal up-conversion luminescence of the three primary colors of red, green and blue. Chinese patent CN111892843A discloses a nanoparticle with a one-core five-shell structure: NaYF4:Yb / Tm@NaYF4@NaYF4:Er / Ho@NaYF4@NaYF4:Nd / Yb / Er@NaYF4:Nd, which can realize orthogonal up-conversion luminescence of the three primary colors of red, green and blue. However, the above nanoluminescent particles have a complex structure and can only realize orthogonal luminescence of the three primary colors in the up-conversion single mode. Summary of the invention

[0005] In view of this, the object of the present invention is to provide a dual-mode orthogonal three-primary color luminescent nanoparticle, a multi-level anti-counterfeiting material, and a preparation method and application thereof. The dual-mode orthogonal three-primary color luminescent nanoparticle provided by the present invention has a core-shell-shell-shell structure, a simple structure, and can achieve dual-mode luminescence of up-conversion green light (or red light) and blue light emission, and down-conversion red light (or green light) emission.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a dual-mode orthogonal tri-primary color luminescent nanoparticle, which comprises, from the inside to the outside, a crystal core, a first emission shell layer, a second emission shell layer and an energy absorption shell layer; the chemical composition of the crystal core is NaGdF4:Yb / Ho / Ce, Ce in the NaGdF4:Yb / Ho / Ce 3+ The concentration is 0.5-40 mol%; the chemical composition of the first emission shell is NaYF4:M, wherein M is Eu or Tb; the chemical composition of the second emission shell is NaYF4:Yb / Tm; the chemical composition of the energy absorption shell is NaYF4:Yb / Nd; the surface of the energy absorption shell is coated with oleic acid.

[0008] Preferably, Yb in the NaGdF4:Yb / Ho / Ce 3+ The concentration of Ho is 15-25 mol%. 3+ The concentration is 0.5~3mol%.

[0009] Preferably, the NaYF4:M3+ The concentration is 1 to 15 mol%.

[0010] Preferably, Yb in the NaYF4:Yb / Tm 3+ The concentration is 20-30 mol%, Tm 3+ The concentration is 0.5~3mol%.

[0011] Preferably, Yb in the NaYF4:Yb / Nd 3+ The concentration of Nd is 5-20 mol%. 3+ The concentration is 40-60 mol%.

[0012] The present invention provides a method for preparing the dual-mode orthogonal three-primary-color luminescent nanoparticles described in the above technical solution, comprising the following steps:

[0013] (1) mixing gadolinium salt, ytterbium salt, holmium salt, cerium salt, oleic acid and 1-octadecene, and performing a first complexation reaction to obtain a nuclear rare earth complex precursor;

[0014] (2) mixing the core rare earth complex precursor with ammonium fluoride, sodium hydroxide and an alcohol solvent, and sequentially performing coprecipitation reactions to obtain NaGdF4:Yb / Ho / Ce;

[0015] (3) mixing sodium trifluoroacetate, yttrium trifluoroacetate, europium trifluoroacetate or terbium trifluoroacetate, oleic acid and 1-octadecene, and performing a second complexation reaction to obtain a first emission shell rare earth complex precursor;

[0016] (4) mixing the first shell rare earth complex precursor with the NaGdF4:Yb / Ho / Ce, and performing a first thermal decomposition reaction to obtain NaGdF4:Yb / Ho / Ce@NaYF4:M;

[0017] (5) mixing sodium trifluoroacetate, yttrium trifluoroacetate, ytterbium trifluoroacetate, thulium trifluoroacetate, oleic acid and 1-octadecene, and performing a third complexation reaction to obtain a second emission shell rare earth complex precursor;

[0018] (6) mixing the second shell rare earth complex precursor with the NaGdF4:Yb / Ho / Ce@NaYF4:M, and performing a second thermal decomposition reaction to obtain NaGdF4:Yb / Ho / Ce@NaYF4:M@NaYF4:Yb / Tm;

[0019] (7) mixing sodium trifluoroacetate, yttrium trifluoroacetate, ytterbium trifluoroacetate, neodymium trifluoroacetate, oleic acid and 1-octadecene, and performing a fourth complexation reaction to obtain an energy absorbing shell rare earth complex precursor;

[0020] (8) mixing the energy absorption shell rare earth complex precursor with the NaGdF4:Yb / Ho / Ce@NaYF4:M@NaYF4:Yb / Tm, and performing a third thermal decomposition reaction to obtain the dual-mode orthogonal tri-primary color luminescent nanoparticles;

[0021] There is no chronological order for steps (1), (3), (5) and (7);

[0022] There is no chronological order for steps (2) to (3);

[0023] There is no chronological order for steps (4) to (5);

[0024] There is no chronological order for steps (6) to (7).

[0025] The present invention provides a dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticle, which is obtained by removing the surface ligands of the dual-mode orthogonal tri-primary color luminescent nanoparticle described in the above technical scheme or the dual-mode orthogonal tri-primary color luminescent nanoparticle prepared by the preparation method described in the above technical scheme by inorganic acid.

[0026] The present invention provides a multi-level anti-counterfeiting material, comprising the dual-mode orthogonal three-primary-color luminescent ligand-free nanoparticles and aqueous glue described in the above technical solution.

[0027] The present invention also provides the use of the dual-mode orthogonal three-primary-color luminescent nanoparticles described in the above technical scheme, the dual-mode orthogonal three-primary-color luminescent nanoparticles prepared by the preparation method described in the above technical scheme, the dual-mode orthogonal three-primary-color luminescent ligand-free nanoparticles described in the above technical scheme, or the multi-level anti-counterfeiting material described in the above technical scheme in information encoding, information encryption, information decryption, multi-level anti-counterfeiting or fluorescent patterned display.

[0028] The present invention provides a dual-mode orthogonal tri-primary color luminescent nanoparticle, which comprises, from the inside to the outside, a crystal core, a first emission shell layer, a second emission shell layer and an energy absorption shell layer; the chemical composition of the crystal core is NaGdF4:Yb / Ho / Ce, Ce in the NaGdF4:Yb / Ho / Ce 3+ The concentration is 0.5-40 mol%; the chemical composition of the first emission shell is NaYF4:M, wherein M is Eu or Tb; the chemical composition of the second emission shell is NaYF4:Yb / Tm; the chemical composition of the energy absorption shell is NaYF4:Yb / Nd; the surface of the energy absorption shell is coated with oleic acid. Compared with the prior art, the dual-mode orthogonal tri-color luminescent nanoparticles provided by the present invention have the following characteristics and beneficial technical effects: In the nanoparticles provided by the present invention, the crystal core has the multifunctional function of regulating red and green light, and by regulating Ce in the crystal core 3+The ion concentration further regulates the emission of red and green light from the crystal core. The first emission shell is a multifunctional shell, which has the dual functions of a red light (or green light) emission layer and an inert protective layer. When M in the first emission shell is Eu, the functions of the nanoparticles from the inside to the outside are: a green light emitting crystal core, a red light emitting layer, a blue light emitting layer, and an 808nm excitation light energy absorption layer; when M is Tb, the functions of the nanoparticles from the inside to the outside are: a red light emitting crystal core, a green light emitting layer, a blue light emitting layer, and an 808nm excitation light energy absorption layer. The present invention utilizes Gd in the crystal core. 3+ The interfacial energy transfer characteristics of Ce 3+ Ions and Ho 3+ The cross-relaxation process between ions and the multifunctionality of the first emission shell have an important influence on the Ce 3+ The ion concentration is increased, the green light emission of the crystal core is converted into red light emission, and the Eu introduced into the first emission shell can be 3+ To achieve red light emission, the Tb introduced into the first emission shell 3+ ions realize green light emission, and realize that at the level of a single nanoparticle, with a simple core-shell-shell-shell multilayer structure, it can respond under near-infrared wavelength and near-ultraviolet wavelength excitation, and achieve upconversion (green light and blue light or red light and blue light) / downtransfer (red light or green light) dual-mode orthogonal three-primary color luminescence, which solves the key problem that conventional orthogonal luminescent nanoparticles have strict dependence on the composition and spatial distribution of rare earth ions, and the problem that traditional core-shell structure luminescent materials need to construct complex multi-layer core-shell structures to achieve orthogonal three-primary color luminescence. The dual-mode orthogonal three-primary color luminescent nanoparticles provided by the present invention have a simple structure and flexible luminescent performance. Not only can the three-primary color luminescent layer be integrated into a single nanoparticle, but also the mutual interference between the three luminescent processes is reduced or avoided, and the generation of orthogonal upconversion / downtransfer fluorescence of the three primary colors of red, green and blue is achieved under the excitation of three different wavelengths of light. The nanoparticles provided by the present invention can emit red, green and blue light at the single particle level; Yb in the crystal core 3+ After absorbing the 980nm excitation light, the ions transfer the energy to Ho 3+ The ions emit green light, and the nanoparticles only emit green light; Ce in the crystal core 3+ After absorbing the 254nm excitation light, the ions transfer the energy to the Gd in the same layer. 3+ Then through Gd 3+ The interfacial energy transfer characteristics transfer energy to Eu in the first emission shell 3+ The ions emit red light, and the nanoparticles only emit red light; the Nd 3+ After absorbing the 980nm excitation light, the ions transfer the energy to the Yb in the same layer. 3+ The ions then transfer the energy to the Yb 3+ ions are then transferred to Tm3+ The ions emit blue light, and the nanoparticles only emit blue light; the energy absorption shell can absorb the energy of the 808nm excitation light, and can also inhibit the quenching of luminescence by surface defects, thereby improving the luminescence efficiency; the nanoparticles provided by the present invention can realize orthogonal red, green and blue luminescence of the nanoparticles by switching the wavelength of the excitation light, and can maintain the up-conversion orthogonal green-blue luminescence performance in a large power range (980nm excitation holding power is 16.9-109.7W·cm -2 ; 808nm excitation holding power is 4.0~86.8W·cm -2 ). The near-infrared excitation sources with wavelengths of 980nm and 808nm and the near-ultraviolet excitation source with wavelengths of 254nm are used to excite the Yb 3+ Ions, Ce 3 + Ions and the third shell of Nd 3+ ions, can realize high-color pure green, red and blue three-primary color luminescence of the crystal core, the first emission shell layer and the second emission shell layer, avoiding the harmful energy crosstalk caused by the excitation light source to realize the orthogonal three-primary color luminescence. The present invention uses the epitaxial coating of the optically inert shell layer to greatly reduce the surface defects of the rare earth up-conversion core nanocrystals, and effectively avoids the crosstalk of harmful ion energy between layers, thereby greatly improving the luminescence brightness of the up-conversion nanocrystals, so that the dual-mode orthogonal three-primary color luminescent nanoparticles have a good application prospect in information security protection; the nanoparticles provided by the present invention have a simple structure, realize dual-mode luminescence, and can also greatly simplify the difficulty of synthesizing nanoparticles.

[0029] The present invention provides a method for preparing the dual-mode orthogonal tri-primary color luminescent nanoparticles described in the above technical solution. The present invention adopts a coprecipitation-thermal decomposition method to prepare dual-mode orthogonal tri-primary color luminescent nanoparticles having a simple core-shell-shell-shell-shell three-shell structure, and up-conversion (green light and blue light or red light and blue light) / down-conversion (red light or green light) responsive to near-infrared wavelength and near-ultraviolet wavelength excitation, which greatly simplifies the synthesis difficulty of orthogonal tri-primary color luminescent nanoparticles, realizes the controllable synthesis of orthogonal tri-primary color luminescent nanoparticles, and is suitable for industrial production.

[0030] The present invention provides a dual-mode orthogonal three-primary color luminescent ligand-free nanoparticle, which is obtained by removing the surface ligand of the dual-mode orthogonal three-primary color luminescent nanoparticle described in the above technical solution or the dual-mode orthogonal three-primary color luminescent nanoparticle prepared by the preparation method described in the above technical solution with inorganic acid. The outer molecular layer of the dual-mode orthogonal three-primary color luminescent nanoparticle is a hydrophobic group and is not miscible with water. The dual-mode orthogonal three-primary color luminescent ligand-free nanoparticle obtained by surface modification treatment of the nanoparticle with inorganic acid in the present invention has significantly improved hydrophilicity and is miscible with water. It is applied to anti-counterfeiting materials to significantly improve the storage stability and luminescence stability of the anti-counterfeiting materials. The dual-mode orthogonal three-primary color luminescent ligand-free nanoparticle provided by the present invention can not only integrate the three-primary color luminescent layer into a single nanoparticle, but also reduce or avoid mutual interference between the three luminescence processes, and realize the generation of orthogonal up-conversion / down-transfer fluorescence of the three primary colors of red, green and blue under the excitation of three different wavelengths of light.

[0031] The present invention provides a multi-level anti-counterfeiting material, comprising the above-mentioned dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticles and aqueous glue. Compared with the prior art, the multi-level anti-counterfeiting material provided by the present invention has the following advantages: the dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticles used in the present invention have strong hydrophilicity and can be miscible with water, thereby improving the storage stability and luminescent stability of the anti-counterfeiting material. 3+ The interfacial energy transfer characteristics of Ce 3+ with Ho 3+The cross-relaxation between the two and the multifunctional effect of the first emission shell layer enable the multi-level anti-counterfeiting material to not only generate independent three-primary color up-conversion / down-transfer luminescence under three different excitation wavelengths (980nm, 808nm, 254nm), but also enable a variety of information to be encrypted in different emission modes and generate multiple levels of coding capabilities. After printing, printing or writing anti-counterfeiting patterns (such as fluorescent patterns or handwriting) using the multi-level anti-counterfeiting material with dual-mode red, green and blue orthogonal three-primary color luminescence characteristics provided by the present invention, these anti-counterfeiting patterns are invisible and unrecognizable under natural light, and anti-counterfeiting patterns of corresponding colors will be presented under different and specific external environmental conditions. For example, by combining the scanning technology of a 3D printer and the image acquisition technology of a digital camera, the fluorescent pattern display of the three primary colors of red, green and blue can be realized under the excitation of 980nm, 808nm near-infrared light and 254nm near-ultraviolet light, which greatly increases the difficulty of decoding and deciphering, further improves the security and level of anti-counterfeiting, and at the same time effectively prevents the anti-counterfeiting pattern after identification from being copied, and has high stability under natural light. The anti-counterfeiting material provided by the present invention not only expands the application scope of orthogonal luminescent nanomaterials, provides technical support for their applications in information encoding, information encryption, information decryption, multi-level anti-counterfeiting or fluorescent patterned display, but also solves the problems of poor fluorescence stability, single anti-counterfeiting technology, low security and easy duplication in traditional anti-counterfeiting materials, greatly improves the level of security and anti-counterfeiting, and can be used for multi-level anti-counterfeiting of many confidential information. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the structure and luminescence principle of dual-mode orthogonal three-primary color luminescent nanoparticles (M is Eu or Tb);

[0033] Figure 2 X-ray diffraction patterns of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%), NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%), NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%) and NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) prepared in Example 1;

[0034] Figure 3Transmission electron micrographs of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) (a), NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) @NaYF4:Eu (15 mol%) (b), NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) @NaYF4:Eu (15 mol%) @NaYF4:Yb / Tm (30 / 1 mol%) (c) and NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) @NaYF4:Eu (15 mol%) @NaYF4:Yb / Tm (30 / 1 mol%) @NaYF4:Yb / Nd (10 / 40 mol%) (d) prepared in Example 1 and the corresponding particle size distribution;

[0035] Figure 4 Normalized spectra and luminescence diagrams of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) prepared in Examples 1 to 2 under excitation at 980 nm, 808 nm and 254 nm, wherein d represents the thickness of the first emission shell, and d=0 represents a crystal core;

[0036] Figure 5 Spectra of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) prepared in Example 1 excited by a 980 nm laser at different power densities;

[0037] Figure 6 Spectra of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) prepared in Example 1 excited by 808 nm laser at different power densities;

[0038] Figure 7 The normalized spectrum of the first emission shell thickness-controlled NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) prepared in Example 1;

[0039] Figure 8The spectrum of NaGdF4:Yb / Ho / Ce (20 / 2 / x mol%, x=2, 8, 16, 24, 30, 34)@NaYF4:Eu (15 mol%) prepared in Example 3 under 980 nm excitation;

[0040] Fig. 9 Normalized spectra of NaGdF4:Yb / Ho / Ce (20 / 2 / 28 mol%)@NaYF4:Tb (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) core-shell-shell-shell nanoparticles prepared in Example 4 under 980 nm, 808 nm and 254 nm excitation;

[0041] Fig.10 FTIR images of the dual-mode orthogonal tri-primary color luminescent nanoparticles prepared in Example 1 and the dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticles prepared therefrom;

[0042] Fig.11 The fluorescent anti-counterfeiting pattern is obtained by screen printing of the anti-counterfeiting material prepared in Example 5, wherein the nanoparticles used in a1-a3 are the dual-mode orthogonal three-primary color luminescent nanoparticles prepared in Example 1, the nanoparticles used in b1-b3 are NaYF4:Yb / Tm (30 / 1 mol%) @NaYF4:Yb / Nd (10 / 40 mol%), the nanoparticles used in c1-c3 are NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) @NaYF4:Eu (15 mol%), and the nanoparticles used in d1-d3 are a physical mixture of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) @NaYF4:Eu (15 mol%) and NaYF4:Yb / Tm (30 / 1 mol%) @NaYF4:Yb / Nd (10 / 40 mol%);

[0043] Fig.12 This is a fluorescent anti-counterfeiting two-dimensional code image obtained by screen printing on the multi-level anti-counterfeiting material prepared in Example 5 for cultural relics protection. DETAILED DESCRIPTION

[0044] The present invention provides a dual-mode orthogonal tri-primary color luminescent nanoparticle, which comprises, from the inside to the outside, a crystal core, a first emission shell layer, a second emission shell layer and an energy absorption shell layer; the chemical composition of the crystal core is NaGdF4:Yb / Ho / Ce, Ce in the NaGdF4:Yb / Ho / Ce 3+The concentration is 0.5-40 mol%; the chemical composition of the first emission shell is NaYF4:M, wherein M is Eu or Tb; the chemical composition of the second emission shell is NaYF4:Yb / Tm; the chemical composition of the energy absorption shell is NaYF4:Yb / Nd; the surface of the energy absorption shell is coated with oleic acid.

[0045] In the present invention, the crystal nucleus is Yb 3+ 、Ho 3+ and Ce 3+ The doped NaGdF4 matrix has a hexagonal phase structure. In the present invention, the chemical composition of the crystal core is NaGdF4:Yb / Ho / Ce, and Yb 3+ The concentration of Ho in NaGdF4:Yb / Ho / Ce is preferably 15-25 mol%, more preferably 18-22 mol%, and further preferably 20 mol%. 3+ The concentration of Ce in the NaGdF4:Yb / Ho / Ce is preferably 0.5 to 3 mol%, more preferably 1 to 2.5 mol%, and further preferably 1.5 to 2 mol%. 3+ The concentration of Ho is 0.5~40mol% 3+ ion green emission, the Ce 3+ The concentration of Ho is preferably 1 to 20 mol%, more preferably 2 to 5 mol%; 3+ Ion red emission, the Ce 3+ The concentration of Ce is preferably 12 to 40 mol%, more preferably 20 to 30 mol%. In the present invention, when Ce in the crystal nucleus 3+ When the concentration is low (≤10 mol%), the crystal core maintains green light emission under 980 nm wavelength excitation, and is a green light emitting crystal core. The crystal core is also able to emit green light in a wide range of excitation power density (16.9-109.7 W·cm -2 ) can maintain good color purity; with the Ce in the crystal core 3+ As the concentration increases (>12mol%), Ce 3+ Able to regulate and Ho 3+ The cross relaxation between them causes the crystal core to change from green light emission to red light emission, forming a red light emission crystal core, and Ce 3+ The higher the concentration, the higher the Ho 3+ The higher the red light color purity, the more effective it is for the Eu introduced into the first emission shell layer. 3+ and Tb 3+ Ion realization Eu 3+ ion red emission and Tb 3+Ion green light emission realizes red, green and blue orthogonal luminescence of two different chemical expressions. In the present invention, the diameter of the crystal core is preferably 8 to 15 nm, more preferably 9 to 12 nm.

[0046] In the present invention, the first emission shell is Eu 3+ or Tb 3+ The chemical composition of the first emission shell layer is NaYF4:M, wherein M is Eu or Tb. 3+ The concentration of Eu is preferably 1 to 15 mol%; when M is Eu, the Eu 3+ The concentration of is more preferably 8 to 15 mol%, and further preferably 10 to 15 mol%; when M is Tb, the 3+ The concentration is more preferably 1 to 12 mol%, and further preferably 2 to 7 mol%. In the present invention, the thickness of the first emission shell is preferably 6 to 10 nm, and more preferably 7.5 to 8.5 mm. In the present invention, when M is Eu, the first emission shell is both an optically inert layer and a red light emitting layer, which can effectively avoid harmful energy crosstalk between the crystal core and the second emission shell while maintaining red light emission under 254 nm wavelength excitation. In the dual-mode orthogonal tri-primary color luminescent nanoparticles provided by the present invention, the inert protective effect of the first emission shell is used to regulate the shell thickness. When the thickness of the first emission shell is 6 to 10 nm, 980 nm and 808 nm near-infrared lasers and 254 nm near-ultraviolet excitation light are used as excitation sources to respectively excite the Yb in the crystal core. 3+ Ions, Ce 3+ Ions and the third shell of Nd 3+ ions, realizing high-color pure green, red and blue luminescence of the crystal core, the first emission shell and the second emission shell, avoiding the harmful energy crosstalk caused by the excitation light source to achieve orthogonal three-primary color luminescence, making it more potential in practical applications such as information security protection.

[0047] In the present invention, the second emission shell is Yb 3+ and Tm 3+ The chemical composition of the second emission shell layer is NaYF4:Yb / Tm. In the present invention, Yb 3+ The concentration of Tm in the NaYF4:Yb / Tm is preferably 20 to 30 mol%, more preferably 22 to 30 mol%, and further preferably 25 to 30 mol%. 3+The concentration of is preferably 0.5-3 mol%, more preferably 0.6-2 mol%, and further preferably 0.8-1 mol%. In the present invention, the thickness of the second emission shell layer is preferably 2.5-4.7 nm, more preferably 3-4 nm. In the present invention, the second emission shell layer maintains blue light emission under 808 nm wavelength excitation, and has a wide excitation power density range (4.0-86.8 W·cm -2 ) Maintain good color purity.

[0048] In the present invention, the energy absorbing shell is Yb 3+ 、Nd 3+ The doped NaYF4 matrix, the chemical composition of the energy absorption shell is NaYF4:Yb / Nd; the surface of the energy absorption shell is coated with oleic acid. In the present invention, Yb in the NaYF4:Yb / Nd 3+ The concentration of Nd in the NaYF4:Yb / Nd is preferably 5 to 20 mol%, more preferably 8 to 18 mol%, and further preferably 10 to 15 mol%. 3+ The concentration is preferably 40-60 mol%, more preferably 40-55 mol%, and further preferably 40-50 mol%. In the present invention, the molar percentage of oleic acid in the energy absorption shell is preferably 1-3%, more preferably 1.5-2.5%. In the present invention, the thickness of the energy absorption shell is preferably 3.1-5.3 nm, more preferably 3.5-5 nm. In the present invention, the energy absorption shell can absorb the 808 nm excitation light energy and can also inhibit surface quenching.

[0049] In the present invention, the particle size of the dual-mode orthogonal three-primary color luminescent nanoparticles is preferably 30 to 45 nm, and more preferably 32 to 40 nm.

[0050] Figure 1 The schematic diagram of the structure and the schematic diagram of the luminescence principle of the dual-mode orthogonal tri-primary color luminescent nanoparticles (M is Eu or Tb) provided by the present invention is as follows: Figure 1 It can be seen that the nanoparticles provided by the present invention have a core-shell-shell-shell structure, which includes a green light (or red light) emitting core NaGdF4:Yb / Ho / Ce, a red light (or green light) emitting layer NaYF4:Eu (or Tb), a blue light emitting layer NaYF4:Yb / Tm and an 808nm excitation light energy absorption layer NaYF4:Yb / Nd from the inside to the outside. The chemical expression is NaGdF4:Yb / Ho / Ce@NaYF4:M(Eu or Tb)@NaYF4:Yb / Tm@NaYF4:Yb / Nd. When M is Eu, Yb in the core is 3+ After absorbing the 980nm excitation light, the ions transfer the energy to Ho 3+The ions emit green light, and the sample only emits green light; low concentration Ce in the crystal core 3+ After absorbing the 254nm excitation light, the ions transfer the energy to the Eu in the first shell. 3+ The ions emit red light, and the sample only emits red light; Nd in the third shell 3+ After absorbing the 980nm excitation light, the ions transfer the energy to the Yb in the same layer. 3+ The ion then transfers the energy to the Yb 3+ ions are then transferred to Tm 3+ The ions emit blue light, and the sample only emits blue light. When M is Tb, the Yb 3+ After absorbing the 980nm excitation light, the ions transfer the energy to Ho 3+ The ions emit red light, and the sample only emits red light; the high concentration of Ce in the crystal core 3+ The ions absorb the 254nm excitation light and transfer the energy to the Tb in the first shell. 3+ The ions emit green light, and the sample only emits green light; Nd 3+ After absorbing the 980nm excitation light, the ions transfer the energy to the Yb in the same layer. 3+ The ion then transfers the energy to the Yb 3+ ions are then transferred to Tm 3+ The ions emit blue light, and the sample only emits blue light. Since the thickness of the first shell is adjusted to avoid harmful energy crosstalk, the color of the nanoparticles can be changed by simply switching the wavelength of the excitation light, thereby achieving up-conversion of green (red) and blue, and down-conversion of red (green) orthogonal luminescence.

[0051] The present invention adjusts the Ce in the crystal nucleus 3+ The doping concentration and the thickness of the first emission shell layer and the second emission shell layer achieve upconversion / downtransfer multi-mode orthogonal green, blue and red full-color emission under 980nm, 808nm and 254nm selective excitation at the single nanoparticle level; moreover, these red, green and blue orthogonal emissions do not depend on the excitation power density and have high color purity. In the application of security and anti-counterfeiting identification, they can greatly increase the security level of the anti-counterfeiting system and the complexity of the anti-counterfeiting mode, and have potential application prospects. It solves the energy crosstalk and single upconversion luminescence mode caused by the core-shell structure in the traditional design, and provides technical support for coding, anti-counterfeiting, information encryption, decryption, full-color display and other aspects. And increase the Ce of the above materials 3+ Concentration, for Ho 3+ To adjust the luminescent color, and to change the Eu 3+ Change to Tb 3+ Another type of nanocrystal with a four-layer core-shell structure and orthogonal red, green and blue luminescence characteristics can also be achieved.

[0052] The present invention provides a method for preparing the dual-mode orthogonal three-primary-color luminescent nanoparticles described in the above technical solution, comprising the following steps:

[0053] (1) mixing gadolinium salt, ytterbium salt, holmium salt, cerium salt, oleic acid and 1-octadecene, and performing a first complexation reaction to obtain a nuclear rare earth complex precursor;

[0054] (2) mixing the core rare earth complex precursor with ammonium fluoride, sodium hydroxide and an alcohol solvent, and sequentially performing coprecipitation reactions to obtain NaGdF4:Yb / Ho / Ce;

[0055] (3) mixing sodium trifluoroacetate, yttrium trifluoroacetate, europium trifluoroacetate or terbium trifluoroacetate, oleic acid and 1-octadecene, and performing a second complexation reaction to obtain a first shell rare earth complex precursor;

[0056] (4) mixing the first shell rare earth complex precursor with the NaGdF4:Yb / Ho / Ce, and performing a first thermal decomposition reaction to obtain NaGdF4:Yb / Ho / Ce@NaYF4:M;

[0057] (5) mixing sodium trifluoroacetate, yttrium trifluoroacetate, ytterbium trifluoroacetate, thulium trifluoroacetate, oleic acid and 1-octadecene, and performing a third complexation reaction to obtain a second shell rare earth complex precursor;

[0058] (6) mixing the second shell rare earth complex precursor with the NaGdF4:Yb / Ho / Ce@NaYF4:M, and performing a second thermal decomposition reaction to obtain NaGdF4:Yb / Ho / Ce@NaYF4:M@NaYF4:Yb / Tm;

[0059] (7) mixing sodium trifluoroacetate, yttrium trifluoroacetate, ytterbium trifluoroacetate, neodymium trifluoroacetate, oleic acid and 1-octadecene, and performing a fourth complexation reaction to obtain an energy absorbing shell rare earth complex precursor;

[0060] (8) mixing the energy absorption shell rare earth complex precursor with the NaGdF4:Yb / Ho / Ce@NaYF4:M@NaYF4:Yb / Tm, and performing a third thermal decomposition reaction to obtain the dual-mode orthogonal tri-primary color luminescent nanoparticles;

[0061] There is no chronological order for steps (1), (3), (5) and (7);

[0062] There is no chronological order for steps (2) to (3);

[0063] There is no chronological order for steps (4) to (5);

[0064] There is no chronological order for steps (6) to (7).

[0065] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.

[0066] The present invention mixes gadolinium salt, ytterbium salt, holmium salt, cerium salt, oleic acid and 1-octadecene (referred to as the first mixing), performs the first complexation reaction, and obtains a nuclear rare earth complex precursor. In the present invention, the gadolinium salt is preferably a water-soluble gadolinium salt and / or an acetic acid-soluble gadolinium salt, more preferably including one or more of gadolinium acetate, gadolinium carbonate and gadolinium nitrate. In the present invention, the ytterbium salt is preferably a water-soluble ytterbium salt and / or an acetic acid-soluble ytterbium salt, more preferably including one or more of ytterbium acetate, ytterbium carbonate and ytterbium nitrate. In the present invention, the holmium salt is preferably a water-soluble holmium salt and / or an acetic acid-soluble holmium salt, more preferably including one or more of holmium acetate, holmium carbonate and holmium nitrate. In the present invention, the cerium salt is preferably a water-soluble cerium salt and / or an acetic acid-soluble cerium salt, more preferably including one or more of cerium acetate, cerium carbonate and cerium nitrate. In the present invention, the gadolinium salt, ytterbium salt, holmium salt and cerium salt are preferably used in the form of gadolinium salt solution, ytterbium salt solution, holmium salt solution and cerium salt solution, respectively. The concentrations of the gadolinium salt solution and the ytterbium salt solution are independently preferably 0.1-0.3 mol / L, more preferably 0.15-0.25 mol / L; the concentration of the holmium salt solution is preferably 0.01-0.03 mol / L, more preferably 0.01-0.02 mol / L; the concentration of the cerium salt solution is preferably 0.1-0.3 mol / L, more preferably 0.1-0.2 mol / L; the solvents in the gadolinium salt solution, the ytterbium salt solution, the holmium salt solution and the cerium salt solution are independently preferably acetic acid and / or water. In the present invention, the gadolinium salt, ytterbium salt, holmium salt and cerium salt are preferably prepared according to the concentrations of Gd, Yb, Ho and Ce in the aforementioned NaGdF4:Yb / Ho / Ce, respectively, and will not be repeated here. In the present invention, the molar ratio of gadolinium acetate to oleic acid is preferably 1:(0.01-0.03), more preferably 1:(0.013-0.023). In the present invention, the volume ratio of oleic acid to 1-octadecene is 1:(0.8-2), more preferably 1:(1-1.5). In the present invention, the first mixing is preferably stirring mixing, and the stirring mixing speed is preferably 130-160r / min, more preferably 140-150r / min; the present invention does not specifically limit the stirring mixing time, as long as the raw materials can be mixed evenly. In the present invention, the temperature of the first complex reaction is preferably 140-160°C, more preferably 150°C, and the time of the first complex reaction is preferably 50-60 minutes, more preferably 50-55 minutes. After completing the first complex reaction, the present invention preferably further comprises cooling the obtained first complex reaction liquid to below 50°C (more preferably room temperature) to obtain a nuclear rare earth complex precursor.

[0067] After obtaining the nuclear rare earth complex precursor, the present invention mixes the nuclear rare earth complex precursor with ammonium fluoride, sodium hydroxide and an alcohol solvent (referred to as the second mixing) to perform a coprecipitation reaction to obtain NaGdF4:Yb / Ho / Ce. In the present invention, the ammonium fluoride is preferably used in the form of an ammonium fluoride solution, and the concentration of the ammonium fluoride solution is preferably 0.3-0.6 mol / L, more preferably 0.4-0.5 mol / L; the solvent in the ammonium fluoride solution preferably includes a propanol solution and a methanol solution; the molar ratio of the gadolinium acetate to the ammonium fluoride is preferably 1:(3.5-5), more preferably 1:(4-5). In the present invention, the sodium hydroxide is preferably used in the form of a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is preferably 0.3-0.6 mol / L, more preferably 0.4-0.5 mol / L; the solvent in the sodium hydroxide solution preferably includes an alcohol solvent, more preferably includes one or more of methanol and propanol; the sodium hydroxide solution is preferably obtained by ultrasonic mixing of sodium hydroxide and a solvent, and the temperature of the ultrasonic mixing is preferably 35-50°C, the power is preferably 2000-2500W, and the time is preferably 20-30min. In the present invention, the molar ratio of gadolinium acetate to sodium hydroxide is preferably 1:(1-1.5), more preferably 1:(1-1.3). In the present invention, the second mixing is preferably stirring mixing, and the stirring mixing speed is preferably 300-360r / min, more preferably 320-330r / min; the present invention has no special limitation on the stirring mixing time, as long as the raw materials can be mixed evenly. In the present invention, the temperature of the coprecipitation reaction is preferably 40 to 50°C, more preferably 50°C, and the time of the coprecipitation reaction is preferably 40 to 60 minutes, more preferably 40 to 50 minutes. After completing the coprecipitation reaction, the present invention preferably further comprises post-treatment, and the post-treatment preferably comprises: subjecting the obtained coprecipitation reaction liquid to desolventization, vacuumization and protective atmosphere in sequence; the desolventization treatment is preferably carried out under heating conditions, the heating temperature is preferably 90 to 100°C, more preferably 95 to 100°C, the heating time is preferably 25 to 40 minutes, more preferably 30 to 35 minutes; the vacuumization time is preferably 4 to 6 minutes, more preferably 5 minutes; the protective atmosphere filling time is preferably 1 to 2 minutes, more preferably 1 to 1.5 minutes; the protective atmosphere preferably comprises argon or helium; the number of repetitions of vacuumization-protection atmosphere filling is preferably 1 to 3 times, more preferably 2 times. In the present invention, the NaGdF4:Yb / Ho / Ce is preferably stored in cyclohexane or chloroform, which is beneficial to improving the dispersibility of NaGdF4:Yb / Ho / Ce and facilitating storage.

[0068] The present invention mixes sodium trifluoroacetate, yttrium trifluoroacetate, europium trifluoroacetate or terbium trifluoroacetate, oleic acid and 1-octadecene (referred to as the third mixture), and performs a second complexation reaction to obtain a first shell rare earth complex precursor. In the present invention, the sodium trifluoroacetate, yttrium trifluoroacetate and europium trifluoroacetate are preferably used in the form of sodium trifluoroacetate solution, yttrium trifluoroacetate solution and europium trifluoroacetate solution, respectively, and the concentrations of the sodium trifluoroacetate solution, yttrium trifluoroacetate solution and europium trifluoroacetate solution are independently preferably 0.2-1.2 mol / L, more preferably 0.5-1 mol / L; the solvents in the sodium trifluoroacetate solution, yttrium trifluoroacetate solution and europium trifluoroacetate solution are independently preferably trifluoroacetic acid and / or water. In the present invention, Na, Y and M (Eu or Tb) are used respectively, and the sodium trifluoroacetate, yttrium trifluoroacetate, europium trifluoroacetate or terbium trifluoroacetate are preferably prepared with the concentrations of Na, Y and M (Eu or Tb) in the NaYF4:M. In the present invention, the molar ratio of yttrium trifluoroacetate to oleic acid is preferably 1: (0.01-0.03), more preferably 1: (0.013-0.023). In the present invention, the volume ratio of oleic acid to 1-octadecene is 1: (0.8-2), more preferably 1: (1-1.5). In the present invention, the third mixing is preferably stirring mixing, and the stirring mixing speed is preferably 280-320 r / min, more preferably 290-300 r / min; the present invention has no special limitation on the stirring mixing time, as long as the raw materials can be mixed evenly. In the present invention, the temperature of the second complex reaction is preferably 110-120°C, more preferably 115-120°C, and the time of the second complex reaction is preferably 30-40 minutes, more preferably 30-35 minutes. After completing the second complex reaction, the present invention preferably further comprises cooling the obtained second complex reaction liquid to below 50°C (more preferably room temperature) to obtain a first shell rare earth complex precursor.

[0069] After obtaining NaGdF4:Yb / Ho / Ce and the first shell rare earth complex precursor, the present invention mixes the first shell rare earth complex precursor with the NaGdF4:Yb / Ho / Ce (referred to as the fourth mixing), and performs a first thermal decomposition reaction to obtain NaGdF4:Yb / Ho / Ce@NaYF4:M. In the present invention, the molar ratio of the NaGdF4:Yb / Ho / Ce to the first shell rare earth complex precursor is preferably 1:(1-5), more preferably 1:(3-4). In the present invention, the method and rotation speed of the fourth mixing are preferably the same as those of the third mixing, and will not be repeated here. In the present invention, the first thermal decomposition reaction preferably includes a pretreatment, and the pretreatment preferably includes: subjecting the obtained mixed solution to desolventizing treatment, vacuuming and filling with a protective atmosphere in sequence; the desolventizing treatment is preferably carried out under heating conditions, and the heating temperature is preferably 100-110°C, more preferably 105-110°C, and the heating time is preferably 20-30min, more preferably 20-25min; the vacuuming time is preferably 20-30min, more preferably 20-25min; the protective atmosphere filling time is preferably 1-2min, more preferably 1-1.5min; the protective atmosphere preferably includes argon or helium. In the present invention, the temperature of the first thermal decomposition is preferably 300-320°C, more preferably 310-320°C; the heating rate from room temperature to the first thermal decomposition reaction temperature is preferably 8-12°C / min, more preferably 10-11°C / min; the insulation time of the first thermal decomposition reaction is preferably 40-50min, more preferably 40-45min; the first thermal decomposition reaction is preferably carried out under a protective atmosphere, and the protective atmosphere preferably includes helium or argon. In the present invention, the NaGdF4:Yb / Ho / Ce@NaYF4:M is preferably stored in cyclohexane or chloroform, which is beneficial to improve the dispersibility of NaGdF4:Yb / Ho / Ce@NaYF4:M and is easy to store.

[0070] The present invention mixes sodium trifluoroacetate, yttrium trifluoroacetate, ytterbium trifluoroacetate, thulium trifluoroacetate, oleic acid and 1-octadecene (referred to as the fifth mixture), performs a third complexation reaction, and obtains a second shell rare earth complex precursor; the second shell rare earth complex precursor is mixed with the NaGdF4:Yb / Ho / Ce@NaYF4:M (referred to as the sixth mixture), performs a second thermal decomposition reaction, and obtains NaGdF4:Yb / Ho / Ce@NaYF4:M@NaYF4:Yb / Tm. In the present invention, the sodium trifluoroacetate, yttrium trifluoroacetate, ytterbium trifluoroacetate and thulium trifluoroacetate are preferably used in the form of sodium trifluoroacetate solution, yttrium trifluoroacetate solution, ytterbium trifluoroacetate solution and thulium trifluoroacetate solution, respectively. The concentrations of the sodium trifluoroacetate solution, yttrium trifluoroacetate solution, ytterbium trifluoroacetate solution and thulium trifluoroacetate solution are independently preferably 0.2-1.2 mol / L, more preferably 0.5-1 mol / L; the solvents in the sodium trifluoroacetate solution, yttrium trifluoroacetate solution, ytterbium trifluoroacetate solution and thulium trifluoroacetate solution are independently preferably trifluoroacetic acid solution and deionized water. In terms of Na, Y, Yb and Tm, the sodium trifluoroacetate, yttrium trifluoroacetate, ytterbium trifluoroacetate and thulium trifluoroacetate are preferably prepared according to the concentrations of Na, Y, Yb and Tm in the NaYF4:Yb / Tm. In the present invention, the molar ratio of yttrium trifluoroacetate to oleic acid is preferably 1:(0.01-0.03), more preferably 1:(0.013-0.023). In the present invention, the molar ratio of NaGdF4:Yb / Ho / Ce to the second shell rare earth complex precursor is preferably 1:(2-4), more preferably 1:2. In the present invention, the other preparation conditions of the second shell rare earth complex precursor and NaGdF4:Yb / Ho / Ce@NaYF4:M@NaYF4:Yb / Tm are preferably the same as the preparation conditions of the first shell rare earth complex precursor in step (2) and the NaGdF4:Yb / Ho / Ce@NaYF4:M in step (3), and will not be repeated here. In the present invention, the NaGdF4:Yb / Ho / Ce@NaYF4:M@NaYF4:Yb / Tm is preferably stored in cyclohexane or chloroform, which is beneficial to improve the dispersibility of NaGdF4:Yb / Ho / Ce@NaYF4:M@NaYF4:Yb / Tm and is easy to preserve.

[0071] The present invention mixes sodium trifluoroacetate, yttrium trifluoroacetate, ytterbium trifluoroacetate, neodymium trifluoroacetate, oleic acid and 1-octadecene (recorded as the seventh mixing), performs a fourth complexation reaction, and obtains an energy absorption shell rare earth complex precursor; the energy absorption shell rare earth complex precursor is mixed with the NaGdF4:Yb / Ho / Ce@NaYF4:M@NaYF4:Yb / Tm (recorded as the eighth mixing), performs a third thermal decomposition reaction, and obtains the dual-mode orthogonal tri-primary color luminescent nanoparticles. In the present invention, the sodium trifluoroacetate, yttrium trifluoroacetate, ytterbium trifluoroacetate and neodymium trifluoroacetate are preferably prepared according to the concentrations of Na, Y, Yb and Nd in NaYF4:Yb / Nd. In the present invention, the molar ratio of the NaGdF4:Yb / Ho / Ce to the energy absorption shell rare earth complex precursor is preferably 1:(2-4), and more preferably 1:(2-3). In the present invention, the other preparation conditions of the energy absorption shell rare earth complex precursor and the dual-mode orthogonal tri-primary color luminescent nanoparticles are preferably the same as the preparation conditions of the first shell rare earth complex precursor in step (2) and the NaGdF4:Yb / Ho / Ce@NaYF4:M in step (3), and are not repeated here. In the present invention, the dual-mode orthogonal tri-primary color luminescent nanoparticles are preferably stored in cyclohexane or chloroform, which is beneficial to improve the dispersibility of the dual-mode orthogonal tri-primary color luminescent nanoparticles and is easy to store and perform subsequent performance tests.

[0072] The present invention provides a dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticle, which is obtained by removing the surface ligands of the dual-mode orthogonal tri-primary color luminescent nanoparticle described in the above technical scheme or the dual-mode orthogonal tri-primary color luminescent nanoparticle prepared by the preparation method described in the above technical scheme by inorganic acid.

[0073] In the present invention, the inorganic acid preferably includes hydrochloric acid and / or sulfuric acid, and the inorganic acid is preferably used in the form of an inorganic acid aqueous solution, and the concentration of the inorganic acid aqueous solution is preferably 1 to 2 mol / L, more preferably 1 to 1.5 mol / L. In the present invention, the mass ratio of the dual-mode orthogonal tri-primary color luminescent nanoparticles to the inorganic acid is preferably 1: (0.5 to 1), more preferably 1: (0.8 to 1).

[0074] The outer molecular layer of the dual-mode orthogonal tri-primary color luminescent nanoparticles modified with oleic acid ligands is a hydrophobic group, which is not miscible with water, and the oleic acid ligands absorb near-ultraviolet energy, which will affect the emission of down-shifted red light under 254nm excitation. The present invention uses inorganic acid to remove the surface ligands of the dual-mode orthogonal tri-primary color luminescent nanoparticles, protonates the oleic acid ligands on the surface of the nanoparticle sample, significantly improves the hydrophilicity of the obtained dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticles, makes them miscible with water, and the prepared anti-counterfeiting material has high stability.

[0075] In the present invention, the preparation method of the dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticles preferably comprises the following steps: mixing the dual-mode orthogonal tri-primary color luminescent nanoparticles, inorganic acid and organic solvent, performing surface ligand removal treatment, and obtaining the dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticles. In the present invention, the organic solvent preferably comprises ethanol and / or acetone; the ratio of the mass of the dual-mode orthogonal tri-primary color luminescent nanoparticles to the volume of the alcohol solvent is preferably 1g: 200-400mL, more preferably 1g: 300-400mL. In the present invention, the mixing is preferably dispersing the dual-mode orthogonal tri-primary color luminescent nanoparticles in an alcohol solvent, and ultrasonically mixing the obtained alcohol dispersion with the inorganic acid; the power of the ultrasonic mixing is preferably 2000-2500W, more preferably 2100-2400W; the temperature of the ultrasonic mixing is preferably 35-50°C, more preferably 40-45°C; the time of the ultrasonic mixing is preferably 20-30min, more preferably 25min. In the present invention, the temperature of the surface ligand removal treatment is preferably 35-50°C, more preferably 40-50°C; the time of the ultrasonic mixing is preferably 20-30min, more preferably 25-30min; the power of the ultrasonic mixing is preferably 2000-2500W, more preferably 2100-2400W.

[0076] After completing the surface ligand removal treatment, the present invention preferably further comprises subjecting the obtained surface ligand removal treatment liquid to solid-liquid separation, and sequentially subjecting the obtained solid product to organic solvent washing and water washing to obtain dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticles. The present invention has no special limitation on the solid-liquid separation, and can adopt a solid-liquid separation method well known to those skilled in the art, such as centrifugal separation; the rotation speed of the centrifugal separation is preferably 12000-15000 r / min, more preferably 13000-14000 r / min; the time of the centrifugal separation is preferably 20-30 min, more preferably 25 min. In the present invention, the organic solvent for the organic solvent washing preferably includes ethanol and / or acetone; the number of alcohol washing and water washing is preferably independently 2-3 times, more preferably 3 times.

[0077] The present invention provides a multi-level anti-counterfeiting material, comprising the dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticles and aqueous slurry as described in the above technical solution. In the present invention, the aqueous slurry preferably comprises an aqueous elastic transparent slurry, more preferably an aqueous elastic transparent slurry of TOU-650. In the present invention, the mass ratio of the dual-mode orthogonal tri-primary color luminescent nanoparticles to the aqueous slurry is preferably 1: (2-5), more preferably 1: (3-4).

[0078] In the present invention, the preparation method of the multi-level anti-counterfeiting material preferably comprises the following steps: mixing the dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticles with an aqueous slurry to obtain the multi-level anti-counterfeiting material. The present invention has no particular limitation on the mixing method and conditions, and the raw materials can be mixed evenly, such as stirring and mixing.

[0079] The present invention provides the dual-mode orthogonal three-primary-color luminescent nanoparticles described in the above technical scheme, the dual-mode orthogonal three-primary-color luminescent nanoparticles prepared by the preparation method described in the above technical scheme, the dual-mode orthogonal three-primary-color luminescent ligand-free nanoparticles described in the above technical scheme, the multi-level anti-counterfeiting material described in the above technical scheme, or the multi-level anti-counterfeiting material prepared by the preparation method described in the above technical scheme, and their applications in information encoding, information encryption, information decryption, multi-level anti-counterfeiting or fluorescent patterned display.

[0080] In the present invention, the multi-level anti-counterfeiting material is preferably made into an anti-counterfeiting pattern for application. In the present invention, the method for preparing the anti-counterfeiting pattern preferably includes screen printing, inkjet printing, spin coating or writing; the present invention has no special limitation on the printing or screen printing, and the printing or screen printing operation familiar to those skilled in the art can be used. The anti-counterfeiting pattern made by the present invention can realize the orthogonal fluorescence display of the three primary colors of red, green and blue respectively under the excitation of 254nm near-ultraviolet light and 980nm and 808nm near-infrared light, and will present an anti-counterfeiting fluorescent pattern of the corresponding color under the environmental conditions under different and specific external environmental conditions, which greatly increases the difficulty of decoding and deciphering, further improves the security and level of anti-counterfeiting, and at the same time can effectively prevent the anti-counterfeiting pattern from being copied after identification, and has good application prospects in the fields of information coding, advanced anti-counterfeiting, information encryption, information decryption and fluorescent patterned display.

[0081] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0082] Example 1

[0083] The core-shell-shell-shell structure nanoparticles prepared in this embodiment are mainly composed of hexagonal NaGdF4 and NaYF4 main matrices doped with rare earth ions of specific concentrations in different spaces (the core region is doped with Yb / Ho / Ce, the first emission shell layer is doped with Eu 3+ The second emission shell doping ion is Yb 3+ / Tm 3+ , the third shell doping ion is Yb 3+ / Nd3+ ), the specific preparation steps are as follows:

[0084] S1: In a 100mL double-necked flask, a 0.2mol / L gadolinium acetate solution (0.912mmol), a 0.2mol / L ytterbium acetate solution (0.24mmol), a 0.02mol / L holmium acetate solution (0.024mmol), a 0.1mol / L cerium acetate solution (0.024mmol), 12mL oleic acid and 18mL 1-octadecene were added, transferred to an oil bath at 150°C, and heated at 150r / min for 50min to obtain a nuclear rare earth complex precursor. After cooling to 50°C and keeping stable, 12mL NH4F methanol solution (4.8mmolNH4F) and 6mL NaOH methanol solution (3mmolNaOH) were ultrasonically mixed and quickly added to the core rare earth complex precursor, heated at 50°C and 330r / min for 40min, and then heated at 100°C for 20min to remove methanol, and the process of 5min vacuuming-1min argon filling was repeated twice, and then heated to 280°C in an argon atmosphere and reacted for 1.5h, centrifuged, and the obtained solid product was dispersed in cyclohexane to obtain a NaGdF4:Yb / Ho / Ce (20 / 2 / 2mol%) dispersion with a concentration of 0.1mol / L.

[0085] S2: Add 1 mol / L sodium trifluoroacetate solution (0.4 mmol), 1 mol / L yttrium trifluoroacetate solution (0.34 mmol), 0.5 mol / L europium trifluoroacetate solution (0.06 mmol), 3.3 mL oleic acid and 6.7 mL 1-octadecene into a 50 mL double-necked flask, transfer to an oil bath at 120°C, and heat at 300 r / min for 35 min to obtain a first shell rare earth complex precursor. After cooling to room temperature, 1 mL of the NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) dispersion was added, and the mixture was heated from room temperature to 115°C under a vacuum environment and maintained for 10 min to remove cyclohexane. The mixture was then heated to 320°C at a rate of 10°C / min under an argon atmosphere and kept warm for 45 min. The mixture was centrifuged and the solid product was dispersed in cyclohexane to obtain a NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%) dispersion with a concentration of 0.1 mol / L, wherein the molar ratio of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) to the first shell rare earth complex precursor was 1:4.

[0086] S3: Add 1 mol / L sodium trifluoroacetate solution (0.2 mmol), 1 mol / L yttrium trifluoroacetate solution (0.138 mmol), 1 mol / L ytterbium trifluoroacetate solution (0.06 mmol), 0.5 mol / L thulium trifluoroacetate solution (0.002 mmol), 3.3 mL oleic acid and 6.7 mL 1-octadecene into a 50 mL double-necked flask, transfer to an oil bath at 120°C, and heat at 300 r / min for 35 min to obtain a second shell rare earth complex precursor. After cooling to room temperature, 1 mL of the NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%) dispersion was added, and the mixture was heated to 115°C under vacuum and maintained for 10 min to remove cyclohexane. The mixture was then heated to 320°C at a rate of 10°C / min under argon and kept warm for 45 min. The mixture was centrifuged and the solid product was dispersed in cyclohexane to obtain a NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%) dispersion with a concentration of 0.1 mol / L.

[0087] S4: Add 1 mol / L sodium trifluoroacetate solution (0.2 mmol), 1 mol / L yttrium trifluoroacetate solution (0.1 mmol), 1 mol / L ytterbium trifluoroacetate solution (0.02 mmol), 0.5 mol / L neodymium trifluoroacetate solution (0.08 mmol), 3.3 mL oleic acid and 6.7 mL 1-octadecene into a 50 mL double-necked flask, transfer to an oil bath at 120°C, and heat at 300 r / min for 35 min to obtain an energy absorption shell rare earth complex precursor. After cooling to room temperature, 1 mL of the NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%) dispersion was added, and the mixture was heated to 115°C under vacuum and maintained for 10 min to remove cyclohexane. The mixture was then heated to 320°C at a rate of 10°C / min in an argon atmosphere and maintained for 45 min. The mixture was centrifuged and the solid product was dispersed in cyclohexane to obtain a dispersion of dual-mode orthogonal trichromatic luminescent nanoparticles (NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%)) with a concentration of 0.1 mol / L.

[0088] Example 2

[0089] By utilizing the inert effect of the first emission shell layer and adjusting the thickness of the first emission shell layer, the energy crosstalk between layers under different excitation sources can be effectively avoided, and high-color-purity red, green and blue light can be emitted under 980nm, 808nm and 254nm excitation. The specific steps are as follows:

[0090] The method of Example 1 is used to prepare dual-mode orthogonal tri-primary color luminescent nanoparticles, which differs from Example 1 in that:

[0091] In step S2, the molar coating ratios of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%) core-shell nanoparticles on the crystal core NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) are 1:1, 1:2 and 1:6 respectively;

[0092] The molar coating ratio is 1:1, and the raw materials used for the first shell rare earth complex precursor are: 1 mol / L sodium trifluoroacetate solution (0.1 mmol), 1 mol / L yttrium trifluoroacetate solution (0.085 mmol), 0.5 mol / L europium trifluoroacetate solution (0.015 mmol), 3.3 mL oleic acid and 6.7 mL 1-octadecene;

[0093] The molar coating ratio is 1:2, and the raw materials used for the first shell rare earth complex precursor are: 1 mol / L sodium trifluoroacetate solution (0.2 mmol), 1 mol / L yttrium trifluoroacetate solution (0.17 mmol), 0.5 mol / L europium trifluoroacetate solution (0.03 mmol), 3.3 mL oleic acid and 6.7 mL 1-octadecene;

[0094] The molar coating ratio is 1:6, and the raw materials used for the first shell rare earth complex precursor are: 1 mol / L sodium trifluoroacetate solution (0.6 mmol), 1 mol / L yttrium trifluoroacetate solution (0.51 mmol), 0.5 mol / L europium trifluoroacetate solution (0.09 mmol), 4.95 mL oleic acid and 10.05 mL 1-octadecene;

[0095] Figure 2NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) (nucleus), Na X-ray diffraction patterns of GdF4:Yb / Ho / Ce(20 / 2 / 2mol%)@NaYF4:Eu(15mol%) (core-shell nanoparticles), NaGdF4:Yb / Ho / Ce(20 / 2 / 2mol%)@NaYF4:Eu(15mol%)@NaYF4:Yb / Tm(30 / 1mol%) (core-shell-shell nanoparticles) and NaGdF4:Yb / Ho / Ce(20 / 2 / 2mol%)@NaYF4:Eu(15mol%)@NaYF4:Yb / Tm(30 / 1mol%)@NaYF4:Yb / Nd(10 / 40mol%) (dual-mode orthogonal trichromatic luminescent nanoparticles, core-shell-shell-shell nanoparticles) are shown by Figure 2 It can be seen that the diffraction peaks correspond one-to-one with the hexagonal NaYF4 (JCPDS: 13-0334) standard card, indicating that the dual-mode orthogonal trichromatic luminescent nanoparticles with a core-shell-shell-shell structure prepared in Example 1 are hexagonal pure phase structures.

[0096] Figure 3 Transmission electron micrographs and corresponding particle size distributions of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) (a), NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) @ NaYF4:Eu (15 mol%) (b), NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) @ NaYF4:Eu (15 mol%) @ NaYF4:Yb / Tm (30 / 1 mol%) (c) and NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) @ NaYF4:Eu (15 mol%) @ NaYF4:Yb / Tm (30 / 1 mol%) @ NaYF4:Yb / Nd (10 / 40 mol%) (d) prepared in Example 1. Figure 3 It can be seen that the high-quality epitaxial growth of nanocrystals can be achieved by combining the co-precipitation method with the thermal decomposition method. The diameter of the green light emitting core NaGdF4:Yb / Ho / Ce is 10.2nm, the thickness of the first emission shell NaYF4:Eu is 7.3nm, the thickness of the second emission shell NaYF4:Yb / Tm is 3.0nm, the thickness of the energy absorption shell NaYF4:Yb / Nd is 3.0nm, and the particle size of the dual-mode orthogonal three-primary color luminescent nanoparticles is 8-40nm.

[0097] Figure 4The normalized emission spectrum of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) prepared in Examples 1 to 2, wherein d represents the thickness of the first emission shell, d=0 represents the crystal core, and Figure 4 It can be seen that when the molar coating ratios of NaGdF4:Yb / Ho / Ce (20 / 2 / 2mol%)@NaYF4:Eu (15mol%) core-shell nanoparticles on the crystal core NaGdF4:Yb / Ho / Ce (20 / 2 / 2mol%) are 1:1, 1:2, 1:4 and 1:6, respectively, the thicknesses of the first emission shell are 2.4nm, 4.3nm, 7.3nm and 9.7nm, respectively. The dual-mode orthogonal tri-primary color luminescent nanoparticles prepared by the present invention can emit orthogonal red, green and blue light with high color purity, wherein the color purity of the orthogonal red, green and blue light emitted with high color purity is the highest when the molar coating ratio is 1:4 (the thickness of the first emission shell is 7.3nm), indicating that the thickness of the first emission shell is 7.3nm, which can effectively suppress harmful energy crosstalk between layers.

[0098] Figure 5 The spectrum of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) prepared in Example 1 under the excitation of 980 nm laser with different power densities is shown in Figure 1. Figure 5 It can be seen that the dual-mode orthogonal tri-primary color luminescent nanoparticles provided by the present invention emit up-converted green light with high color purity under 980nm excitation; emit up-converted blue light with high color purity under 808nm excitation; and emit down-converted red light with high color purity under 254nm excitation. This shows that the dual-mode orthogonal tri-primary color luminescent nanoparticles provided by the present invention can emit red, green and blue light with high color purity under corresponding excitation conditions, effectively avoiding the color impurity caused by energy crosstalk between layers.

[0099] Figure 6 The spectrum of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) prepared in Example 1 under the excitation of 808 nm laser with different power densities is shown in Figure 1. Figure 6It can be seen that NaGdF4:Yb / Ho / Ce(20 / 2 / 2mol%)@NaYF4:Eu(15mol%)@NaYF4:Yb / Tm(30 / 1mol%)@NaYF4:Yb / Nd(10 / 40mol%) can be used in a large power range (16.9~109.7W·cm -2 ) maintains green light emission under 980nm excitation.

[0100] Figure 7 The normalized spectrum of the first emission shell thickness-controlled NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) prepared in Example 1 is given by Figure 7 It can be seen that NaGdF4:Yb / Ho / Ce(20 / 2 / 2mol%)@NaYF4:Eu(15mol%)@NaYF4:Yb / Tm(30 / 1mol%)@NaYF4:Yb / Nd(10 / 40mol%) can be used in a large power range (4.0~86.8W·cm -2 ) maintains blue light emission under 808nm excitation.

[0101] Example 3

[0102] By regulating the Ce in the crystal core 3+ The concentration of ions is obtained by 980nm excitation in the nucleus. 3+ The preferred doping concentration for the transition of ion green light emission to red light emission is as follows:

[0103] The dual-mode orthogonal tri-primary color luminescent nanoparticles were prepared according to the method of Example 1, and the only difference from Example 1 was that:

[0104] In step S1, the molar ratio of gadolinium acetate, ytterbium acetate, holmium acetate and cerium acetate is (78-x)%:20%:2%:x%, wherein x is 2, 8, 16, 24, 30 and 34, respectively, and the total molar amount of gadolinium acetate, ytterbium acetate, holmium acetate and cerium acetate is 0.4 mmol, 4 mL of oleic acid, 6 mL of 1-octadecene, 4 mL of NH4F methanol solution (1.6 mmol NH4F), and 2 mL of NaOH methanol solution (1 mmol NaOH) are used to obtain a NaGdF4:Yb / Ho / Ce (20 / 2 / x mol%, x=2, 8, 16, 24, 30, 34) dispersion.

[0105] In step S2, NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) is replaced by NaGdF4:Yb / Ho / Ce (20 / 2 / x mol%, x=2, 8, 16, 24, 30, 34), and the thermal decomposition reaction time is 40 min to obtain NaGdF4:Yb / Ho / Ce (20 / 2 / x mol%, x=2, 8, 16, 24, 30, 34)@NaYF4:Eu (15 mol%) dispersion.

[0106] Figure 8 The spectrum of NaGdF4:Yb / Ho / Ce (20 / 2 / x mol%, x=2, 8, 16, 24, 30, 34)@NaYF4:Eu (15 mol%) core-shell nanoparticles prepared in Example 3 under 980 nm excitation. Figure 8 It can be seen that increasing Ce 3+ Ion concentration, Ho under 980nm excitation 3+ The ion light changes from green to red. 3+ Ion green emission Ce 3+ The preferred concentration of ions is 2 mol% for Ho 3+ Ion red emission Ce 3+ The preferred concentration of ions is 28 mol%.

[0107] Example 4

[0108] In the dual-mode orthogonal tri-color luminescent nanoparticles prepared in this embodiment, Ce in NaGdF4:Yb / Ho / Ce 3+ The concentration is 28 mol%. The Eu doped in the first emission shell layer of Example 1 3+ Replace with Tb 3+ The specific steps include:

[0109] The dual-mode orthogonal tri-primary color luminescent nanoparticles were prepared according to the method of Example 1, and the only difference from Example 1 was that:

[0110] In step S1, 0.6 mmol of gadolinium acetate and 0.336 mmol of cerium acetate were added to obtain a NaGdF4:Yb / Ho / Ce (20 / 2 / 28 mol%) dispersion.

[0111] In step S2, europium trifluoroacetate is replaced with terbium trifluoroacetate to obtain a NaGdF4:Yb / Ho / Ce (20 / 2 / 28 mol%)@NaYF4:Tb (15 mol%) dispersion.

[0112] Fig. 9The normalized spectra of NaGdF4:Yb / Ho / Ce (20 / 2 / 28 mol%)@NaYF4:Tb (15 mol%)@NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) prepared in Example 4 under 980 nm, 808 nm and 254 nm excitation are shown in FIG. Fig. 9 It can be seen that NaGdF4:Yb / Ho / Ce (20 / 2 / 28 mol%) @NaYF4:Tb (15 mol%) @NaYF4:Yb / Tm (30 / 1 mol%) @NaYF4:Yb / Nd (10 / 40 mol%) emits high color purity up-conversion red light under 980nm excitation; emits high color purity up-conversion blue light under 808nm excitation; and emits high color purity down-conversion green light under 254nm excitation. It shows that the dual-mode orthogonal tri-color luminescent nanoparticles provided by the present invention can emit high color purity red, green and blue luminescence under corresponding excitation conditions, and high color purity orthogonal red, green and blue luminescence can also be obtained by changing the concentration of rare earth ions doped in the crystal core and the type of rare earth ions doped in the luminescent layer, which solves the key problem that conventional orthogonal luminescent nanoparticles have strict dependence on the composition and spatial distribution of rare earth ions, thereby realizing a simple and flexible design and material synthesis of orthogonal luminescent materials.

[0113] Comparative Example 1

[0114] Preparation of NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) nanoparticles:

[0115] S1: In a 50mL double-necked flask, 0.2mol / L yttrium acetate solution (0.276mmol), 0.2mol / L ytterbium acetate solution (0.12mmol), 0.02mol / L thulium acetate solution (0.004mmol), 3.3mL oleic acid and 6.7mL 1-octadecene were added, transferred to an oil bath at 150°C, and heated at 150r / min for 50min to obtain a nuclear rare earth complex precursor. After cooling to 50°C and keeping stable, 4mL NH4F methanol solution (1.6mmol NH4F) and 2mL NaOH methanol solution (1mmol NaOH) were ultrasonically mixed and quickly added to the nuclear rare earth complex precursor. The mixture was heated at 50°C and 330r / min for 40min, and then heated at 100°C for 20min to remove the methanol. The process of 5min vacuuming and 1min argon filling was repeated twice. The mixture was then heated to 280°C in an argon atmosphere and reacted for 1.5h. The mixture was centrifuged and the solid product was dispersed in cyclohexane to obtain a NaYF4:Yb / Tm (30 / 1mol%) dispersion with a concentration of 0.1mol / L.

[0116] S2: Add 1 mol / L sodium trifluoroacetate solution (0.2 mmol), 1 mol / L yttrium trifluoroacetate solution (0.1 mmol), 1 mol / L ytterbium trifluoroacetate solution (0.02 mmol), 0.5 mol / L neodymium trifluoroacetate solution (0.08 mmol), 3.3 mL oleic acid and 6.7 mL 1-octadecene into a 50 mL double-necked flask, transfer to an oil bath at 120°C, and heat at 300 r / min for 35 min to obtain an energy absorption shell rare earth complex precursor. After cooling to room temperature, 1 mL of the NaYF4:Yb / Tm (30 / 1 mol%) dispersion was added, and the mixture was heated to 115°C under vacuum and maintained for 10 min to remove cyclohexane. The mixture was then heated to 320°C at a rate of 10°C / min in an argon atmosphere and kept warm for 45 min. The mixture was centrifuged and the solid product was dispersed in cyclohexane to obtain a NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) dispersion with a concentration of 0.1 mol / L.

[0117] Comparative Example 2

[0118] Preparation of prepared NaGdF4:Yb / Ho / Ce (20 / 2 / 2mol%)@NaYF4:Eu (15mol%) nanoparticles:

[0119] S1: In a 50mL double-necked flask, a 0.2mol / L gadolinium acetate solution (0.304mmol), a 0.2mol / L ytterbium acetate solution (0.08mmol), a 0.02mol / L holmium acetate solution (0.008mmol), a 0.1mol / L cerium acetate solution (0.008mmol), 4mL oleic acid and 6mL 1-octadecene were added, transferred to an oil bath at 150°C, and heated at 150r / min for 50min to obtain a nuclear rare earth complex precursor. After cooling to 50°C and keeping stable, 4mL of NH4F methanol solution (1.6mmolNH4F) and 2mL of NaOH methanol solution (1mmolNaOH) were ultrasonically mixed and quickly added to the core rare earth complex precursor. The mixture was heated at 50°C and 330r / min for 40min, and then heated at 100°C for 20min to remove the methanol. The process of 5min vacuuming and 1min argon filling was repeated twice. The mixture was then heated to 280°C in an argon atmosphere and reacted for 1.5h. The mixture was centrifuged and the solid product was dispersed in cyclohexane to obtain a NaGdF4:Yb / Ho / Ce (20 / 2 / 2mol%) dispersion with a concentration of 0.1mol / L.

[0120] S2: Add 1 mol / L sodium trifluoroacetate solution (0.2 mmol), 1 mol / L yttrium trifluoroacetate solution (0.17 mmol), 0.5 mol / L europium trifluoroacetate solution (0.03 mmol), 3.3 mL oleic acid and 6.7 mL 1-octadecene into a 50 mL double-necked flask, transfer to an oil bath at 120°C, and heat at 300 r / min for 35 min to obtain a first shell rare earth complex precursor. After cooling to room temperature, 1 mL of the NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) dispersion was added, and the mixture was heated from room temperature to 115°C under vacuum and maintained for 10 min to remove cyclohexane. The mixture was then heated to 320°C at a rate of 10°C / min under argon atmosphere and maintained for 45 min. The mixture was centrifuged and the solid product was dispersed in cyclohexane to obtain a NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%) dispersion with a concentration of 0.1 mol / L.

[0121] Comparative Example 3

[0122] Preparation of physical mixture of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%) and NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%):

[0123] Add 0.5 mL of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%)@NaYF4:Eu (15 mol%) nanoparticle dispersion to 0.5 mL of NaYF4:Yb / Tm (30 / 1 mol%)@NaYF4:Yb / Nd (10 / 40 mol%) nanoparticle dispersion and shake well.

[0124] Example 5

[0125] 1 mL of the nanoparticle dispersion was dispersed in 1 mL of ethanol, 1 mL of a 2 mol / L hydrochloric acid aqueous solution was added, and the mixture was ultrasonically treated at 40°C and 2100 W for 20 min, and centrifuged at 15000 r / min for 20 min. The obtained solid product was washed with anhydrous ethanol 3 times and deionized water 3 times to obtain dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticles; wherein the nanoparticles were the dual-mode orthogonal tri-primary color luminescent nanoparticles prepared in Example 1, the NaGdF4:Yb / Ho / Ce prepared in Comparative Example 1, and the nanoparticles were prepared in Example 1. (20 / 2 / 2mol%)@NaYF4:Eu (15mol%), NaGdF4:Yb / Ho / Ce (20 / 2 / 2mol%)@NaYF4:Eu (15mol%) prepared in Comparative Example 2, a physical mixture of NaGdF4:Yb / Ho / Ce (20 / 2 / 2mol%)@NaYF4:Eu (15mol%) prepared in Comparative Example 3 and NaYF4:Yb / Tm (30 / 1mol%)@NaYF4:Yb / Nd (10 / 40mol%).

[0126] The dual-mode orthogonal three-primary-color luminescent ligand-free nanoparticles and TOU-650 water-based elastic transparent adhesive are uniformly mixed in a volume ratio of 1:2 to obtain a multi-level anti-counterfeiting material.

[0127] Fig.10 The Fourier transform infrared spectra (FTIR) of the dual-mode orthogonal tri-primary color luminescent nanoparticles (UCNPs with oleic acid ligands) prepared in Example 1 and the dual-mode orthogonal tri-primary color luminescent nanoparticles (UCNPs without oleic acid ligands) prepared therefrom are shown in FIG. Fig.10 It can be seen that after inorganic acid treatment, the characteristic peaks of the CH bond and C=O bond in the oleic acid ligand basically disappeared after the surface ligand was removed, and the OH vibration peak of the water molecule was enhanced because the UCNPs without oleic acid ligand were dispersed in water and there were adsorbed water molecules on the surface, indicating that inorganic acid treatment can remove the oleic acid ligand coated on the surface of the nanoparticles.

[0128] Fig.11The fluorescent anti-counterfeiting pattern is obtained by screen printing of the anti-counterfeiting material prepared in Example 5, wherein the nanoparticles used in a1 to a3 are the dual-mode orthogonal three-primary color luminescent nanoparticles prepared in Example 1, the nanoparticles used in b1 to b3 are NaYF4:Yb / Tm (30 / 1 mol%) @NaYF4:Yb / Nd (10 / 40 mol%), the nanoparticles used in c1 to c3 are NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) @NaYF4:Eu (15 mol%), and the nanoparticles used in d1 to d3 are a physical mixture of NaGdF4:Yb / Ho / Ce (20 / 2 / 2 mol%) @NaYF4:Eu (15 mol%) and NaYF4:Yb / Tm (30 / 1 mol%) @NaYF4:Yb / Nd (10 / 40 mol%). Fig.11 It can be seen that the pattern of the multi-level anti-counterfeiting material prepared by the present invention is colorless and invisible under natural light, but can present three primary colors of fluorescent patterns respectively under the excitation of three different wavelengths of light. Fig.11 It can be seen from a1 to a3 that the four-leaf clover printed on photographic paper by the multi-level anti-counterfeiting material provided by the present invention presents a green fluorescent pattern under the excitation of 980nm wavelength, a blue fluorescent pattern under the excitation of 808nm wavelength, and a red fluorescent pattern under the excitation of 254nm wavelength, and has higher brightness and purity than the multi-level anti-counterfeiting materials of other comparison samples.

[0129] Fig.12 This is a fluorescent anti-counterfeiting two-dimensional code image obtained by screen printing on the multi-level anti-counterfeiting material prepared in Example 5 (using the dual-mode orthogonal three-primary color luminescent nanoparticles prepared in Example 1) for cultural relics protection. Fig.11 It can be seen that on cultural relics, the anti-counterfeiting QR code is colorless and invisible under natural light and cannot be recognized, but under different and specific external environments, it will present corresponding anti-counterfeiting QR codes with different luminous colors, and the information points of each part of the presented anti-counterfeiting QR code are different, which greatly improves the protection level of cultural relics and information replication.

[0130] In summary, in the nanoparticles provided by the present invention, the crystal core has the multifunctional function of regulating red and green light. 3+The ion concentration further regulates the emission of red and green light. The first emission shell is a multifunctional shell, which has the dual functions of a red (or green) emission layer and an inert protective layer. The present invention sets the excitation light absorption of the crystal core and each shell layer, the emission of three-primary color fluorescence, the isolation function between layers, the rare earth ion doping ratio and concentration of the crystal core and each shell layer. The preparation method provided by the present invention can realize the controllable synthesis of the crystal core and multiple shell layers of the nanoparticles, and prepare a simple core-shell-shell-shell-shell multilayer structure with a specific doping concentration and core-shell size, which has an orthogonal red, green and blue three-primary color up-conversion / down-transfer luminescence dual-mode orthogonal three-primary color luminescent nanoparticles (OUCNPs) that respond to excitation under near-infrared wavelengths and near-ultraviolet wavelengths, solving the core technical problems of harmful energy crosstalk between layers caused by near-infrared excitation light sources and the influence of excitation power density in traditional designs. In the specific preparation process, a combination of co-precipitation and thermal decomposition methods was used to prepare a four-layer core-shell structured nanomaterial with orthogonal red, green and blue primary colors up-conversion / down-transfer luminescence that responds to near-infrared and near-ultraviolet wavelengths through layer-by-layer coating, thereby achieving the purpose of designing a suitable core-shell structure to achieve three-primary color up-conversion / down-transfer luminescence.

[0131] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A dual-mode orthogonal three-primary color luminescent nanoparticle, comprising, from inside to outside: A crystal core, a first emitting shell, a second emitting shell and an energy absorbing shell; The chemical composition of the crystal core is NaGdF4:Yb / Ho / Ce, wherein Ce 3+ The concentration of Yb is 0.5~40mol%. 3+ The concentration of Ho is 15~25mol%. 3+ The concentration is 0.5~3mol; The chemical composition of the first emission shell layer is NaYF4:M, wherein M is Eu or Tb, and M in the NaYF4:M 3+ The concentration is 1~15mol%; The chemical composition of the second emission shell layer is NaYF4:Yb / Tm, wherein Yb 3+ The concentration is 20~30mol%, Tm 3+ The concentration is 0.5~3mol; The chemical composition of the energy absorption shell is NaYF4:Yb / Nd, wherein Yb 3+ The concentration of Nd is 5~20mol%. 3+ The concentration is 40-60 mol%; the surface of the energy absorption shell layer is coated with oleic acid.

2. The method for preparing the dual-mode orthogonal three-primary color luminescent nanoparticles according to claim 1 comprises the following steps: (1) mixing gadolinium salt, ytterbium salt, holmium salt, cerium salt, oleic acid and 1-octadecene, and performing a first complexation reaction to obtain a nuclear rare earth complex precursor; (2) mixing the core rare earth complex precursor with ammonium fluoride, sodium hydroxide and an alcohol solvent to carry out a coprecipitation reaction to obtain NaGdF4:Yb / Ho / Ce; (3) mixing sodium trifluoroacetate, yttrium trifluoroacetate, europium trifluoroacetate or terbium trifluoroacetate, oleic acid and 1-octadecene, and performing a second complexation reaction to obtain a first emission shell rare earth complex precursor; (4) mixing the first shell rare earth complex precursor with the NaGdF4:Yb / Ho / Ce, and performing a first thermal decomposition reaction to obtain NaGdF4:Yb / Ho / Ce@NaYF4:M; (5) mixing sodium trifluoroacetate, yttrium trifluoroacetate, ytterbium trifluoroacetate, thulium trifluoroacetate, oleic acid and 1-octadecene, and performing a third complexation reaction to obtain a second emission shell rare earth complex precursor; (6) mixing the second shell rare earth complex precursor with the NaGdF4:Yb / Ho / Ce@NaYF4:M, and performing a second thermal decomposition reaction to obtain NaGdF4:Yb / Ho / Ce@NaYF4:M@NaYF4:Yb / Tm; (7) mixing sodium trifluoroacetate, yttrium trifluoroacetate, ytterbium trifluoroacetate, neodymium trifluoroacetate, oleic acid and 1-octadecene, and performing a fourth complexation reaction to obtain an energy absorption shell rare earth complex precursor; (8) mixing the energy absorption shell rare earth complex precursor with the NaGdF4:Yb / Ho / Ce@NaYF4:M@NaYF4:Yb / Tm, and performing a third thermal decomposition reaction to obtain the dual-mode orthogonal tri-primary color luminescent nanoparticles; There is no chronological order for steps (1), (3), (5) and (7); There is no chronological order for steps (2) to (3); There is no chronological order for steps (4) to (5); There is no chronological order for steps (6) to (7).

3. A dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticle, which is obtained by removing the surface ligand of the dual-mode orthogonal tri-primary color luminescent nanoparticle described in claim 1 or the dual-mode orthogonal tri-primary color luminescent nanoparticle prepared by the preparation method described in claim 2 by an inorganic acid.

4. A multi-level anti-counterfeiting material, characterized in that: It comprises the dual-mode orthogonal three-primary-color luminescent ligand-free nanoparticles and aqueous glue as described in claim 3.

5. The multi-level anti-counterfeiting material according to claim 4, characterized in that: The mass ratio of the dual-mode orthogonal tri-primary color luminescent ligand-free nanoparticles to the aqueous slurry is 1:(2-5).

6. Application of the dual-mode orthogonal three-primary-color luminescent nanoparticles according to claim 1, the dual-mode orthogonal three-primary-color luminescent nanoparticles prepared by the preparation method according to claim 2, the dual-mode orthogonal three-primary-color luminescent ligand-free nanoparticles according to claim 3, and the multi-level anti-counterfeiting material according to claim 4 or 5 in information encoding, information encryption, information decryption, multi-level anti-counterfeiting or fluorescent patterned display.

Citation Information

Patent Citations

  • Multistage anti-counterfeiting material with three-primary-color orthogonal up-conversion fluorescence characteristic and application of multistage anti-counterfeiting material

    CN111681532A

  • Method for preparing three-primary-color up-conversion luminescent material with orthogonal excitation-emission response

    CN111808604A

  • Preparation method of red, green and blue three-primary-color orthogonal up-conversion fluorescent safe ink

    CN111892843A